P09.02 Reattendance rates in men presenting with symptoms of urethritis – can point of care testing for chlamydia and gonorrhoea improve outcomes?. (13th September 2015) - Carter, N; Crofts, M; Garrett, F; Clarke, M; Nicholls, J; Wheeler, H; Sharp, D; Horner, P
Abstract : Introduction: Chlamydia and gonorrhoea are common causes of urethritis. Management is often based on an enhanced syndromic approach while awaiting results. This can necessitate prescribing to cover a range of potential pathogens, and uncertainty for patients. Point of care testing (POCT) for chlamydia and gonorrhoea in men with symptoms of urethritis could alter care pathways and reduce reattendance in these patients. The aim of this study was to measure reattendance rates in men presenting with symptoms of urethritis and develop a decision tree care pathway model in order to estimate potential benefits of replacing standard nucleic acid amplification testing with POCT. Methods: All men with urethritis symptoms presenting over a three month period were identified using electronic patient records. Urethritis was defined as ≥5 pmnls/hpf on a Gram stained urethral smear. Reattendances within 30 days of initial clinic visit and reasons for reattendance were recorded for both microscopy-positive and negative groups. Review of literature was used to provide estimates of improved outcomes if the chlamydia/gonorrhoea POCT result was available prior to the clinical consultation. Results: 431 men with urethritis symptoms were identified in a 3 month period. 192 had confirmed urethritis on initial microscopy. 31% of microscopy-positive men and 42% of microscopy-negative men reattended at least once within 30 days of initial visit. Common reasons for reattendance were early morning smear (20%), persistent symptoms (18%), results (16%) and gonorrhoea test of cure (9%). It was estimated that POCT could reduce microscopy by 25% and repeat reattendance following treatment by 75% through improved pathogen-directed treatment and the introduction of gonorrhoea POCT sample drop-off as a test of cure. Conclusion: This service evaluation using decision tree care pathway modelling has identified high reattendance rates in men with urethritis symptoms which POCT has the potential to reduce substantially. Disclosure of interest statement: PH has received funding from Cepheid directly and indirectly for lecturing on point of care testing and undertaking research on the cost effectiveness of their CT/NG assay. Has also received payment from Atlas Genetics for an article in the Parliamentary Review on the benefits of point of care technology in improving the cost effectiveness of sexual health services. Has also received an honorarium from Hologic for an education talk on STI diagnostics. NC, MC, FG, MC, JN, HW, no conflicts of interest declared.